Current Situation and Solutions for Methane (CH4) Emission in Paddy Rice Cultivation in Vietnam - Phu Hao, Dong; Thanh Binh, Nguyen; Hoang Anh, Le (VNU Journal of Science: Earth and Environmental Sciences, 2023)
Abstract: Paddy rice production emits a significant amount of greenhouse gas, particularly methane (CH 4 ). The purpose of this review is to assess the current status of CH 4 emissions from paddy rice cultivation in Vietnam and propose solutions for reducing CH 4 emissions. CH 4 emissions from paddy rice cultivation account for 49.7 million tons of CO 2 eq (CO 2  equivalent) per year in Vietnam. Soil texture, watering regime, and paddy cultivation technique are important in influencing CH 4 emissions. Applications of advanced farming techniques such as the System of Rice Intensification (SRI), Alternate Wetting and Drying (AWD), and the use of biochar are among the recommended solutions. In summary, paddy rice production is the main source of CH 4 emissions, which causes devastating effects on the global climate. Therefore, solutions that may both reduce GHG emissions and increase economic efficiency should be put into practice.